Sequencing and phylogenetic analysis of human group A rotavirus genotypes circulating among diarrheic children in Edo State, Nigeria - Osazee Izevbuwa (Microbes and Infectious Diseases, 2023)
rotaviruses are one of the vital causative agents of acute gastroenteritis (AGE) in young children worldwide. Genotyping of detected RVA strains is needed for a more extensive knowledge of the epidemiology of rotaviral infections. This descriptive cross-sectional study aimed to evaluate the circulation of RVA genotypes in diarrheic children living in Edo State, Nigeria. A total of 400 stool samples collected from children less than five years with acute diarrhea were initially screened for RVA antigen by immumochromatographic method, and the RVA antigen-positive samples were subsequently analyzed using Reverse Transcription Polymerase Chain Reaction (RT-PCR), multiplex PCR and sequencing of the VP7 and VP4 gene segments of the RVA strains. Phylogenetic trees were constructed from the nucleotide sequences using the neighbor joining algorithm in MEGA software, version 6. Seventeen stool samples were confirmed as RVA-positive by the first round RT-PCR out of the twenty RVA antigen-positive samples that were examined. Based on RT-PCR assay, the prevalence of RVA which caused diarrhea in children less than five years was estimated at 4.25%. All the 17 stool samples that were confirmed RVA-positive by first round RT-PCR were successfully genotyped for VP7-G and VP4-P genes. Multiplex PCR revealed that G2[P6] was the most frequently found genotype combination (1.50%) rather than the G1[P8] (1.25%) which occurred most frequently worldwide. G9[P6] strains were responsible for 0.50% of RVA prevalence. Unusual RVA strains carrying genotype G2[P8] accounted for a prevalence of 0.50% while mixed infections caused by the G2G9[P6] strains also accounted for a prevalence of 0.50%.